Cd immobilization and soil quality under Fe–modified biochar in weakly alkaline soil. (October 2021) - Sun, Tong; Xu, Yingming; Sun, Yuebing; Wang, Lin; Liang, Xuefeng; Zheng, Shunan
Abstract: Cost–effective and environment–friendly implementation techniques are critical to the success of remediation in large–scale cadmium (Cd) contaminated agricultural soil. Field experiments were conducted to investigate the effect of Fe–modified biochar on Cd bioavailability in soils and uptake by maize ( Zea mays L.), soil aggregate distribution and stability, and microbial community composition in weakly alkaline Cd–contaminated soil. Results showed that Fe–modified biochar optimized the structure and stability of soil aggregates. Moreover, the content of soil organic carbon increased by 6.59%–20.36% when compared with the control groups. However, DTPA–Cd concentration under the treatment of Fe–modified biochar was suffered by 37.74%–41.65% reduction in contrast with CK, and the significant decrease ( P < 0.05) was obtained at 0.5% Fe–modified biochar. Moreover, sequential extraction procedures showed that the acid soluble and reducible states of Cd was converted into oxidizable and residual form. The addition of Fe–modified biochar inhibited Cd accumulation in maize, being 41.31%–76.64% (Zhengdan 958), 38.19%–70.95% (Liyu 86) and 52.30%–59.95% (Sanbei 218) reduction, respectively, in contrast with CK. The activity of catalase, urease and alkaline phosphatase in soil increased gradually with the addition of Fe–modified biochar. The enhancement in the number of soil bacterial OTUs and the values of Shannon, Chao1, ACE index indicated that Fe–modified biochar promoted the richness and diversity of bacterial communities. Therefore, the improvements of soil environment and biological quality indicated that Fe–modified biochar should be an alternative agent on remediation of Cd–contaminated soils. Graphical abstract: Image 1 Highlights: Fe–modified biochar optimized the structure and stability of soil aggregates. The concentration of DTPA–Cd in soil and Cd uptake in maize was inhibited. It could promote the richness and diversity of bacterial communities.